Implementasi Program Aksara Untuk Mempercepat Peningkatan Indeks Pembangunan Manusia (IPM) di Kabupaten Banyuwangi - Muftiyah, Al; Fitriyah, Fitriyah; Handayani, Suci; Nurhayati, Nurhayati; Saputra, Aswin (UKInstitute, 2022)
Community service aims to increase the acceleration of HDI and the welfare of the entire community through the literacy program that has been issued by the Banyuwangi district government with non-formal learning, one of which is PKBM Asri, as well as collaboration with service providers who have carried out socialization and training activities for making knitted mask connector products along with their marketing. capable of providing economic value to society. The benefit for the community itself is business continuity that can improve the quality and standard of living of the community. The methods used are socialization, training, and discussion. The targets are residents of Bedewang village, Songgon district and Temuasri village, Kec. Perfect.